Analisis Pemanfaatan Sampah Bernilai Ekonomis dalam Peningkatan Ekonomi Masyarakat Kota Medan melalui Aplikasi Kepul - Muhammad Rafi Hagi; Rahmat Daim Harahap; Fauzi Arif Lubis (Journal of Islamic Economics and Finance, 2023)
This study aims to describe the use of waste and economic improvement of the people of Medan City through the Kepul Application based on Circular Economy Theory and take data from the study. This study uses qualitative methods with data analysis techniques using qualitative descriptive analysis. The results show that the development of the Kepul application has always been the main thing in the company's mission, this is because of the development of applications according to customer suggestions such as the Live Location feature, re-schedule, membership, etc. The effectiveness of Kepul in increasing people's income is arguably very good, as evidenced by the increase in resource persons' income from the range of Rp. 100,000 to Rp. 800,000 a month. From the results of the study, it is known that there are still many obstacles in Kepul in becoming an intermediary container for waste utilization in Medan City such as lack of strong branding, fleet problems, and price difference problems with conventional collectors. But this obstacle is not an impossible obstacle to pass, with the successful collaboration of Kepul with the Medan City Government and plans to attract more investors, Kepul believes that all the obstacles above can be passed well.